Incidence of thyroid pathologies requiring thyroid surgeries in a tertiary care hospital - Panchal, Anuradha; Ray, Aniket; Gautam, Raj; Shah, Aashay; Singh, Chandan; Chandrashekhar, Shantanu; Shah, Yashraj; Krishna Kumar G., Ashwanth; Shahid, Mehreen (International Surgery Journal, 2020)
Background: Diseases of the thyroid gland are one of the most common endocrine disorders in India and the world, many of these diseases require surgery for their treatment. The incidence of thyroid diseases differs from one geographical area to another. This study was aimed at finding out the thyroid pathologies for which thyroid surgeries were performed in D. Y. Patil Hospital, Nerul, Navi Mumbai. Methods: It is a retrospective analysis of all the patients who have undergone thyroid surgeries (lobectomy, hemithyroidectomy, subtotal or near total thyroidectomy or total thyroidectomy) in D. Y. Patil hospital, Nerul, Navi Mumbai from 1st January 2018 to 31st December 2019 (2 years duration). Results: Most common pathology for which thyroidectomy was performed was colloid goitre (41.33%). Benign diseases of the thyroid was much more common (76%) than malignant diseases (24%). Most common malignancy was papillary carcinoma thyroid. Thyroid surgeries were most commonly performed on women in their 5th decade of life. Conclusions: Colloid goitre was the most common pathology for which thyroid surgeries were performed and females in their 5th decade of life were the most common patients undergoing thyroidectomy.